STUDY OF EARLINESS IN COMMERCIAL COTTON (G. hirsutum L) GENOTYPES - Ali, Ch. Rehmat; Arshad, Muhammad; Khan, Muhammad Idrees; Afzal, Muhammad (Journal of Research (Science), 2003)
The research work was conducted at Central Cotton Research Institute (CCRI), Multan during the normal crop growing season 2002-03, including fourteen varieties, (thirteen from Punjab and one from Sindh province) with the aim to find out the earliness in the said varieties. From the experimental results it is concluded that CIM-443 produced significantly lowest main stem node number of first sympodial branch (4.6) followed by CIM-240 and Karishma (5.7). While the highest main stem node bearing first sympodial branch number was recorded in variety CIM-1100. The less number of days to first flower was taken by variety CIM-443 followed by CIM-240, while the more number of days were recorded in variety CIM-1100. Therefore, it is concluded that CIM-443 is the earliest maturing variety among all the fourteen varieties.